2011
DOI: 10.1039/c0cp02201b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinjection of hydrogen and the nature of a giant shift of the fundamental absorption edge in highly disordered V2O5 films

Abstract: Production of atomic photochemical hydrogen under the action of light and its subsequent injection into transition metal oxides has yielded numerous interesting results. Here we report on the mechanism of the photo-induced hydrogen transfer between adsorbed organic molecules and the surface of highly disordered V(2)O(5) films. We have managed to carry out the photoinjection of hydrogen into the V(2)O(5) films at very low temperatures, which is very important both for investigations of the reaction mechanism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Beta-diketonates, essentially V(acac) 3 and VO(acac) 2 , were intensively investigated for CVD processes under atmospheric and reduced pressures. Both precursors were used in aerosol-assisted (AA)CVD with various solvents.…”
Section: Vanadium Beta-diketonate Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Beta-diketonates, essentially V(acac) 3 and VO(acac) 2 , were intensively investigated for CVD processes under atmospheric and reduced pressures. Both precursors were used in aerosol-assisted (AA)CVD with various solvents.…”
Section: Vanadium Beta-diketonate Compoundsmentioning
confidence: 99%
“…Vanadium alkoxides have been reported as efficient single-source precursors. [168][169][170] Mathur et al have reported on the grown phases starting from the thermal decomposition of vanadium oxo-tri-isopropoxide (VO(O i Pr) 3 ) under reduced pressure. [168] The authors reported the formation of a single-phase coating of V 2 13 was obtained at 600°C, while VO 2 was grown at 700°C.…”
Section: Vanadium Alkoxide Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resulting in deeper coloration due to increased charge transfer; while also, the device may degrade especially due to formation of excess polymeric components for consistent resonant tunneling effects [14][15][16][17][18][19][20]. The EC devices have open circuit memory, and can function without energy for long periods; optical absorption can be tuned between states, but the optical change is slow depending on device size varying from seconds to tens of minutes [3].…”
Section: Electrochromic Smart Windowmentioning
confidence: 99%